2017
DOI: 10.1088/1741-4326/aa7b44
|View full text |Cite
|
Sign up to set email alerts
|

On theρscaling of intrinsic rotation in C-Mod plasmas with edge transport barriers

Abstract: Changes in the core intrinsic toroidal rotation velocity following L-to Hand Lto I-mode transitions have been investigated in Alcator C-Mod tokamak plasmas. The magnitude of the co-current rotation increments is found to increase with the pedestal temperature gradient and q 95 , and to decrease with toroidal magnetic field. These results are captured quantitatively by a model of fluctuation entropy balance which gives the Mach number M i ∼ = ρ * /2 L s /L T ∼ ∇T q 95 /B T in an ITG turbulence dominant regime. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Although the indications of this experiment are that the fast-ions may have contributed to the discrepancy between the dimensionless parameter scan and database results, a direct comparison between the ρ * scaling of intrinsic Mach number at the top of the pedestal and database studies shows some discrepancy still remains. While [23,24] found the Alfvén Mach number to scale as ρ 1 * , the present results shows a scaling of ρ 0 * , which agrees with the older result of [14]. Note that in a dimensionless parameter scan, Mach number and Alfvén Mach number have the same scaling to the extent β has been held constant.…”
Section: ρ * Scaling Of Intrinsic Rotationsupporting
confidence: 87%
See 3 more Smart Citations
“…Although the indications of this experiment are that the fast-ions may have contributed to the discrepancy between the dimensionless parameter scan and database results, a direct comparison between the ρ * scaling of intrinsic Mach number at the top of the pedestal and database studies shows some discrepancy still remains. While [23,24] found the Alfvén Mach number to scale as ρ 1 * , the present results shows a scaling of ρ 0 * , which agrees with the older result of [14]. Note that in a dimensionless parameter scan, Mach number and Alfvén Mach number have the same scaling to the extent β has been held constant.…”
Section: ρ * Scaling Of Intrinsic Rotationsupporting
confidence: 87%
“…As explained in that work, these results were unexpected based on concepts of residual stress driven intrinsic rotation and results from database studies of intrinsic rotation, which found the intrinsic rotation at the top of the pedestal to scale as ρ 0 * [14] or ρ 1 * [23,24]. The results of [25,26] also show a scaling of ρ 1 * if L φ ∼ a, where L φ is the radial scale length of electrostatic fluctuation intensity.…”
Section: ρ * Scaling Of Intrinsic Rotationmentioning
confidence: 79%
See 2 more Smart Citations
“…While toroidal rotation is important for in/out impurity asymmetries, it does not seem to be a factor for the up/down asymmetry. As will be seen in section 3, there is a big difference in the up/down asymmetry between I-and H-mode, while the toroidal rotation (with Mach numbers as large as 0.3) in these two regimes is quite similar [33]. Conversely, the rotation in L-and I-mode is very different [17], while the up/down asymmetry is similar.…”
Section: Experimental Set-upmentioning
confidence: 99%